PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY, GOOD CORPORATE GOVERNANCE, DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN - Hexana Sri Lastanti; Nabil Salim (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2018)
The purpose of this study is to determine the effect of corporate social responsibility disclosure, good corporate governance, dan financial performance towards firm value. Samples were selected using purposive sampling method and acquired 120 companies. Testing the hypothesis in this study is done by using multiple linear regression analysis. This study obtains results that corporate social responsibility disclosure, good corporate governance, and financial performance simultaneously has positive and significant effect on firm value. Good corporate governance proxied with managerial ownership partially has positive and significant effect on firm value, whereas Corporate social responsibility disclosure, Good corporate governance proxied with institutional ownership, proportion of independent board of commissioners, size of board of directors, size of committe, and Financial performance partially don’t have significant effect on firm value.